2011
DOI: 10.1038/nsmb.1983
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis for the assembly of the SMRT/NCoR core transcriptional repression machinery

Abstract: Eukaryotic transcriptional repressors function by recruiting large co-regulatory complexes that target histone deacetylase enzymes to gene promoters/enhancers. Transcriptional repression complexes, assembled by the co-repressor NCoR, and its homologue SMRT, play critical roles in many processes including development and metabolic physiology. The core repression complex involves the recruitment of three proteins: HDAC3, GPS2 and TBL1 to a highly conserved repression domain within SMRT and NCoR. We have used a v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
157
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(164 citation statements)
references
References 61 publications
6
157
1
Order By: Relevance
“…None of these constructs bound to a control NID peptide containing the RTT mutation K305R, confirming specificity. We noted that residues 227-297 of NCoR1, which appear to be involved in binding MeCP2, overlap with the NCoR1 region that interacts with TBL1 and TBLR1 (NCoR1 residues 247-256) (22). This overlap in interaction site suggested that the MeCP2-NCoR1 interaction might be indirect, mediated by interaction of MeCP2 with endogenous TBL1/TBLR1 present in cell lysates.…”
Section: Mecp2mentioning
confidence: 84%
“…None of these constructs bound to a control NID peptide containing the RTT mutation K305R, confirming specificity. We noted that residues 227-297 of NCoR1, which appear to be involved in binding MeCP2, overlap with the NCoR1 region that interacts with TBL1 and TBLR1 (NCoR1 residues 247-256) (22). This overlap in interaction site suggested that the MeCP2-NCoR1 interaction might be indirect, mediated by interaction of MeCP2 with endogenous TBL1/TBLR1 present in cell lysates.…”
Section: Mecp2mentioning
confidence: 84%
“…Recent biochemical studies have highlighted the assembly of the subunit GPS2 into both SMRT and NCOR1 complexes and suggest a structural core function of GPS2 in both (49). However, ChIP assays combined with RNAi also indicated the existence of SMRT and NCOR1 complexes, along with the HDAC3, TBL1, and TBLR1 subunits, that occupied different genes -in macrophages or hepatocytes -despite the lack of GPS2 (29,34).…”
Section: Figurementioning
confidence: 99%
“…Both proteins contain a LisH domain. LisH-dependent dimerization has been observed for several proteins (Kim et al, 2004;Mikolajka et al, 2006;Oberoi et al, 2011;Delto et al, 2015). This data suggests that the LisH domains encoded by AT5G09630 and AT4G37880 mediate their selfinteraction.…”
Section: Identification Of Mrctlh Components In Arabidopsis Thalianamentioning
confidence: 89%